Prácticas Sociales Sobre la Salud Bucal en Mamás de la Etnia Yanacona del Municipio de Pitalito, Huila (2021)
Human societies are an agglomeration of interests, made up of men and women whose events are related to three objective categories, which constitute social practices, these categories are: social agents, the world of objects and the objective conditions of the social life. Social practices when producing, forming or maintaining women, men and material conditions, thus establish the rules of the social game exercised by the objective conditions themselves.